Intra organisational perceptions of affirmative action - Leopeng, Selwalephuthi Peter (My University, 2014)
Recent developments in South Africa and the impending changes in the workplace, have placed new challenges and demands on managers of both big and small organisations. One of these challenges is the introduction and implementation of successful Affirmative Action (AA) programme. However, preparatory to this, it is important to gain an understanding of the perceptions of employees concerning AA because the way perceptions of employees may influence the manner in which such programmes are implemented in companies. The Employment Equity Act No. 55 (Republic of South Africa, 1998) makes it clear that every designated employer must, in order to achieve employment equity, implement AA measures. A survey method was used in this study, and opinions were sought from 209 supervisors and junior managers at Eskom Head Office, Megawatt Park. The results were analysed quantitatively in order to gain an insight into their perceptions of issues concerning AA. The results reveal that there are differences of opinion about AA amongst the junior and middle management employees. The differences are mainly racially based. There is no common understanding of AA and this leads to a dysfunctional effort in the implementation of this change. As resistance to change is a natural behavior of organisations and its members, naturally AA can be expected to be resisted by most employees. The present study suggests ways to overcome this problem and identifies the need for intervention to be undertaken concerning changing perceptions before AA can be understood and successfully implemented .
Thesis (M.B.A.)--University of the Witwatersrand, 1999.
Keywords: Affirmative action programs--South Africa; Discrimination in employment--South Africa